2022
DOI: 10.1111/jdi.13902
|View full text |Cite
|
Sign up to set email alerts
|

Advances in insulin therapy from discovery to β‐cell replacement

Abstract: Insulin therapy using insulin purified from porcine or bovine pancreas revolutionized diabetes therapy in the 1920s. A series of advances including cloning human insulin cDNA enabled the development of recombinant human insulin with improved features. Insulin treatment for diabetes may well be upended by β‐cell replacement therapy in the coming decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Direct assessments of islet graft BCM remain challenging in current clinical evaluations of transplantation efficacies 12,13 . Recently, the development of exendin‐based GLP‐1R‐targeted β‐cell imaging has shed light on this issue 4,13,14 . However, most studies involving such imaging have focused on insulinoma or the pancreas alone, 16,24,27–29 whereas only a limited number of studies have examined the possibility of islet graft evaluation for IT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct assessments of islet graft BCM remain challenging in current clinical evaluations of transplantation efficacies 12,13 . Recently, the development of exendin‐based GLP‐1R‐targeted β‐cell imaging has shed light on this issue 4,13,14 . However, most studies involving such imaging have focused on insulinoma or the pancreas alone, 16,24,27–29 whereas only a limited number of studies have examined the possibility of islet graft evaluation for IT.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recently, the development of exendinbased GLP-1R-targeted βcell imaging has shed light on this issue. 4,13,14 However, most studies involving such imaging have focused on insulinoma or the pancreas alone, 16,24,[27][28][29] whereas only a limited number of studies have examined the possibility of islet graft evaluation for IT. Eter et al reported that 111 In-exendin-3 SPECT/CT displayed islet grafts in intramuscular IT mice, and the uptake in calf muscle correlated with graft volume 30,31 ; however, muscle is not favorable in IT and intramuscular transplantation remains very uncommon in the clinic.…”
Section: (A) (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…A century has elapsed since the first formulated insulin made a debut. Progressive techniques and materials have overcome many problems of insulin therapy, including impurities, duration of action, antibodies against porcine or bovine insulin, and the expense of production 1 .…”
mentioning
confidence: 99%